The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1074/jbc.m511237200
|View full text |Cite
|
Sign up to set email alerts
|

Human Prolyl-4-hydroxylase α(I) Transcription Is Mediated by Upstream Stimulatory Factors

Abstract: Prolyl-4-hydroxylase ␣(I) (P4H␣(I)) is the rate-limiting subunit for P4H enzyme activity, which is essential for procollagen hydroxylation and secretion. In the current study, we have characterized the human P4H␣(I) promoter for transcription factors and DNA elements regulating P4H␣(I) expression. Using a progressive deletion cloning approach, we have constructed pGL3-P4H␣(I) recombinant plasmids. We have identified a positive regulatory region at the positions of bp ؊184 to ؊97 responsible for ϳ80% of the P4H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 58 publications
(51 reference statements)
1
35
0
1
Order By: Relevance
“…15,16 Previously, we have reported that an E-box-like sequence (CACGGG) located at Ϫ135bp of the P4H␣1 promoter is responsible for 80% of the basal transcriptional activity and appears to be upregulated by TGF␤1 and downregulated by cigarette smoking. 17 In the current study, we investigated the effects of TNF-␣ on P4H␣1 expression and the underlying molecular mechanisms of these effects. We have found that TNF-␣1 suppresses P4H␣1 expression at the transcriptional level.…”
Section: See Page 1677mentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Previously, we have reported that an E-box-like sequence (CACGGG) located at Ϫ135bp of the P4H␣1 promoter is responsible for 80% of the basal transcriptional activity and appears to be upregulated by TGF␤1 and downregulated by cigarette smoking. 17 In the current study, we investigated the effects of TNF-␣ on P4H␣1 expression and the underlying molecular mechanisms of these effects. We have found that TNF-␣1 suppresses P4H␣1 expression at the transcriptional level.…”
Section: See Page 1677mentioning
confidence: 99%
“…The details of the primers and sequence confirmation of these plasmids have been described previously. 17 To define the nucleotides within the region Ϫ32 to ϩ18bp in the P4H␣1 promoter responsible for the binding of TNF-␣ responsive protein NonO, we constructed P4H␣1 promoter pGL3 reporter with serial deletions of Ϫ32 to Ϫ15bp, Ϫ32 to Ϫ3bp. The primers of the region Ϫ15pGL3 vector were sense: GGTAC-CACGGGCTCCCTCTGCTGC CCAG, antisense: GCTAGCAC-CACCACAGCGGGAAGGAATGG.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Based on the enhanceosome concept, we hypothesized that another transcription factor(s) is required to activate HIF target genes during hypoxia. We found that many HIF target genes, including HMOX1 (41,42,63,64,84,88,89,112), SFTPA1 (13,32,33), CXCR4 (73,90,96), PAI1 (2,18,27,29,47,57,58,66), BDNF (48,97), hTERT (3,9,35,44,52,61,67,72,75,110,113), CTSB (111) (107), and P4H␣(I) (10,43,98), are also reported to be activated by the transcription factor upstream stimulatory factor 1 (USF1) or USF2, suggesting a possible role of USF1/USF2 in the hypoxic response.USFs (USF1 and USF2) are basic helix-loop-helix-leucine zipper (bHLH-LZ) transcription factors that are expressed ubiquitously, albeit at different levels depending on the tissue type (14,36,94,95,101 (7,8,19) as either USF1/USF1 or USF2/USF2 homodimers or USF1/USF2 heterodimers. The major functional USF complexes in most cell types are USF1/USF2 heterodimers (94, 101).…”
mentioning
confidence: 99%
“…It can form homo-and heterodimers and recognize in vitro a CACGTG core sequence termed E box (31). Through binding to E boxes of target genes, USF2 has been demonstrated to regulate expression of many genes (4,9,10,13,17,22,23,34,39). In our previous studies, we demonstrated that high-glucose exposure stimulated nuclear USF2 accumulation, which mediated high-glucose conditions and induced TSP1 gene expression and TGF-␤ activity in glomerular mesangial cells, suggesting a role of USF2 in the development of diabetic renal complications.…”
Section: Discussionmentioning
confidence: 99%